Forhandlinger ved Lolland-Falsters Forstmandsforenings Møde den 2den Oktober 1869. - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Forhandlinger ved Lolland-Falsters Forstmandsforenings Møde den 2den Oktober 1869.